2022
DOI: 10.1002/stc.2984
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time hybrid simulations including rocking effects: The case of a frame‐structure with unbounded elastomeric isolators

Abstract: Real‐time hybrid simulations (RTHS) have become an attractive alternative for the study of structural systems by conveniently separating an experimental substructure from a numerical component. Due to the technical and economic benefits of applying fiber‐reinforced elastomeric isolators (FREIs) in unbounded configuration, the analysis of this device using RTHS is gaining interest among researchers. However, there are aspects associated with the complexity of the unbounded isolators that alter the dynamic behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Reference Structure. Te reference structure used, shown in Figure 1, was built at the University of Naples Federico II, Italy, with the objective of performing several seismic shake table tests on this structure to evaluate the seismic performance of base isolation systems [16,17,44,45,[69][70][71]. Tis prototype had a scale factor of 1 : 3 for a total height of 2900 mm and a plan area (X-Y) of 2150 × 2650 mm.…”
Section: Main Structurementioning
confidence: 99%
See 4 more Smart Citations
“…Reference Structure. Te reference structure used, shown in Figure 1, was built at the University of Naples Federico II, Italy, with the objective of performing several seismic shake table tests on this structure to evaluate the seismic performance of base isolation systems [16,17,44,45,[69][70][71]. Tis prototype had a scale factor of 1 : 3 for a total height of 2900 mm and a plan area (X-Y) of 2150 × 2650 mm.…”
Section: Main Structurementioning
confidence: 99%
“…Losanno et al [17,44] assessed the seismic behavior of U-FREI devices when subjected to bidirectional excitation, while the reference structure was supported by them, and concluded that these devices have signifcant potential in terms of reduction of the seismic vulnerability of the structure and cost-efectiveness of production using lowcost materials. Riascos et al [45] conducted an RTHS using a numerical model of this structure with the aim of verifying the importance of considering the rocking efect in the behavior of U-FREI devices and concluded that considering this efect represents an increase in the isolator and structure displacement; however, it represents a reduction in the fundamental frequency of the structure and a signifcant increase in the isolation capacity. Calabrese et al [70] performed a comparison between the results obtained in a shake table test and the results of an RTHS test, concluding that the RTHS is highly efective in validating the behavior of U-FREI devices supporting these types of structures.…”
Section: Main Structurementioning
confidence: 99%
See 3 more Smart Citations